2012
DOI: 10.1177/0192513x12444858
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Grandparents With Alzheimer’s Disease

Abstract: This study examined adolescent grandchildren's contributions to caregiving for grandparents with Alzheimer's disease. It was predicted that grandchildren would provide more care when parents experienced greater burden, and when adolescents had higher quality relationships with parents and grandparents. It was also hypothesized that these factors would predict higher levels of social commitment and more positive attitudes toward the provision of long-term care. Twenty-nine adolescents and their parents particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 33 publications
1
53
0
1
Order By: Relevance
“…Hamill found that young adults were willing to become the primary caregiver if required, something also observed in the present study . However, Hamill's participants were younger than the participants in our study.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Hamill found that young adults were willing to become the primary caregiver if required, something also observed in the present study . However, Hamill's participants were younger than the participants in our study.…”
Section: Discussionsupporting
confidence: 73%
“…Most care recipients prefer to live at home and to be cared for by family members . As the primary caregiver in the family might have to work, young adult children and grandchildren often assist in caring for their older RWD or sometimes act as their main caregivers …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respecto a la muestra, predominan los estudios con un tamaño medio de la misma, es decir, aquellos en que el número total de participantes oscila entre los 31 y los 100 individuos, siendo esta aleatoria en solo cuatro de los casos analizados (Boland, 2012;Coppola et al, 2012;Cordella et al, 2012;Jarrott et al, 2012).…”
Section: Resultsunclassified
“…There are sufficient research findings about family caregivers' experience; however, little is known about the experiences of adult family members as their fellow family members provide care to a relative with dementia (Hou et al, 2015). Some studies that have investigated the perceptions of the abovementioned group of individuals were conducted in countries like the United States, China, and Spain where the focus was on participants aged 11 to 25 years (Celdran, Villar, & Triado, 2012;Hamill, 2012;Hou et al, 2015). However, the experiences of adult family members aged between 18 and 41 appear to have received no attention from researchers so far (Hou et al, 2015).…”
Section: Chapter 1: Overviewmentioning
confidence: 99%